QUANTITATIVE ANALYSIS OF NATURAL ANTIOXIDANTS AND FREE RADICAL SCAVENGING ACTIVITIES OF CRUCIFERAE VEGETABLES - KS, Jamuna; CK, Ramesh; Sj, Aditya Rao; M, Paramesha; Mahmood, Riaz (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this research program is to evaluate the antioxidant potentialities comprehensively utilizing commonly available cruciferous vegetables of India, viz., cabbage, cauliflower, kohlrabi, and radish. Methods: The plant materials were procured and processed for cold extraction procedure using 70% ethanol. The extracts were primarily assessed for their phytoconstituents and further for their in vitro antioxidant activity using various qualitative and quantitative estimations. The results of quantitative estimations were expressed in terms of equivalence with respective standards, and the antioxidant potentiality of various scavenging and chelating activities were expressed in terms of 50% effective concentration. Further, correlation studies were made between quantitative and qualitative assays to study the relationship between the effects of different phytoconstituents groups. Results: In this study, the results revealed that all the four cruciferous vegetable extracts possess potential antioxidant activities. Among the extracts under study kohlrabi has recorded superior antioxidant potential than others. It is clear from the study that the tested cruciferous vegetables manifested differential expression of antioxidant capacity due to their phytoconstituents. Conclusion: From the results, it can be concluded that the Cruciferae vegetables have potent antioxidant activity contributing to the use for health benefits in addition to their nutritive role as vegetable. Keywords: Cruciferae vegetables, Phytochemicals, In vitro antioxidant activity, Correlation.